The Role of Internal Auditing in Enhancing the Attractiveness and Competitiveness of Special Economic Zones: An International Comparative Study and Implications for Investment Strategies. - EZZAYRI, MUSTAPHA; EL GHAZALI, M’BARKA (Revue du contrôle, de la comptabilité et de l’audit, 2025)
This study analyzes the role of internal audit in enhancing the attractiveness and competitiveness of Special Economic Zones (SEZs) through a comparative assessment of Morocco, Singapore, Ethiopia, India, and Brazil. Beyond fiscal incentives and infrastructure, the findings emphasize the decisive importance of governance, transparency, and institutional credibility supported by effective internal audit mechanisms. Using an ARDL framework for the period 2016–2024, the results confirm that internal audit strengthens investor confidence by reducing information asymmetry and ensuring compliance with global standards such as OECD Pillar Two. Exports and employment emerge as primary economic drivers, while tax incentives prove effective only when embedded in credible governance systems. Policy recommendations call for moving beyond narrow fiscal paradigms toward integrated governance and compliance strategies to secure SEZs’ long-term competitiveness.